Indigenous food production system and the impact of population growth: community-based examples with anthropological evidence - AHM Zehadul , Karim (2013)
An excessive population growth has a consequential effect on agricultural resource-base, where a huge amount of farming land has drastically been reduced in the past few decades; and that process still continuing. Contextually, I formulate a clear statement saying that due to an excessive demographic pressure, the farmers around the world go for a mechanized cultivation by making an abrupt shift from their indigenous traditional food production system to a more intensive mechanized cultivation. Based on the above contention, I make a conclusive statement with a modest caution saying that we must find some preventive mechanisms to keep our population at a replacement level. This will eventually allow us to revert to our indigenous food production system, which seems to be essential to make our planet earth more natural and habitable for the future. In spite of all upheavals and criticality, in the final part of the paper, I have provided a suggestion for integrating the indigenous food production system with that of the newly-evolved development devices for a better synthesis and fruitful outcome for the human society.